Utilization Efficiency of Yolk Egg on Maanvis (Pterophyllum scalare) Embryos and Larvae in Different Incubation Temperatures - Budiardi, T.; Cahyaningrum, W.; Effendi, I. (Jurnal Akuakultur Indonesia, 2005)
This study was performed to determine the efficiency of yolk egg utilization in embryos and larvae, hatching rate, incubation time to hatch, and growth rate of maanvis (Pterophyllum scalare) larvae incubated at room remperature, 27oC, and 30oC.  Results of study showed that yolk egg utilization efficiency of embryos and larvae incubated at 30oC was 73.70% and 0,18%, respectively, and no different with that of room and 27oC incubation temperatures.  Hatching rate of eggs incubated at 30oC (84.75%) was also same with that of other treatments.  However, incubation time to hatch (27.41 hours) was shorter than that of other treatments.  The growth rate by length of larvae (2.16%) and survival rate (75.28%) incubated at 30oC was also higher compared with that of other treatments.  Thus, in general, optimum temperature for egg hatching and larval rearing of maanvis was 30oC. Keywords: maanvis, Pterophyllum scalare, egg yolk, larvae, embryo, temperature   ABSTRAK Penelitian ini dilakukan untuk mengetahui efisiensi pemanfaatan kuning telur pada embrio dan larva, derajat penetasan, lama inkubasi telur hingga menetas, dan laju pertumbuhan serta kelangsungan hidup larva ikan maanvis (Pterophyllum scalare) yang diinkubasi pada suhu ruang, 27oC dan 30oC.  Hasil penelitian menunjukkan bahwa nilai efisiensi pemanfaatan kuning telur bila diinkubasi pada suhu 30oCsebesar 73,70% pada fase embrio dan 0,18% pada fase larva, dan tidak berbeda dengan suhu ruang dan 27oC.  Demikian juga dengan derajat penetasan telur  (84,75%) tidak berbeda dengan perlakuan lainnya.  Sementara itu, lama inkubasi telur hingga menetas (27,41 jam) lebih cepat dibandingkan dengan suhu inkubasi perlakuan lainnya. Demikian juga dengan laju pertumbuhan panjang (2,16%) dan kelangsungan hidup larva (75,28%) lebih tinggi dibandingkan dengan perlakuan lainnya. Dengan demikian, secara umum suhu optimal untuk penetasan dan pemeliharaan larva ikan maanvis adalah 30°C. Kata kunci: ikan maanvis, Pterophyllum scalare, kuning telur, larva, embrio, suhu